Biodiversitas Pohon Di Repong Damar Krui - Afif Bintoro; Sugeng Prayitno Harianto; Bainah Sari Dewi (Journal of People, Forest and Environment, 2022)
Repong Damar was a land that is managed by the people of Krui, the West Pesisir District, using an agroforestry pattern, was to combine the plant of forest and agriculture or commonly called agroforestry in the same land. The main plant of repong damar was the “damar mata kucing” (Shorea javanica) trees of fruit, and trees of wood product and other plant was medicinal potential. The purpose of this study was to know the biodiversity of trees in Krui, West Pesisir District. The research was conducted in Pekon Pahmungan and Gunung Kemala, Krui on February – June 2021. The method used in this research was survey methods by measuring plots of 25 PU in Pekon Pahmungan and 25 PU in Pekon Gunung Kemala. The results of research in Pahmungan Village, was 18 types of trees species with a total of 241 trees were found, the INP results in Pahmungan Village found 127 damar trees species with 116.74% INP, biodiversity index (H’) was 0,1595, 44 duku trees with 44.36% INP, and H’ was 0,1227, and Bayur trees was 21 trees with an INP of 63.36%, H’ was 0,0954. As for the results of research on Pekon Gunung Kemala, there were 15 types of tree species with a total of 241 trees, the INP results that dominated the Pekon Gunung Kemala found 104 trees with an INP of 190.73%, H’ was 0,1251. Durian trees was 38 trees with an INP was 17.10%, and H’ was 0,0709, and ketupak trees was 15 trees with an INP was 10.00%, and H’ was 0,0492. Repong damar was dominate of trees and the main trees was being “damar mata kucing” (Shorea javanica). The conclution of this research that the biodiversity of repong damar Krui were low